Infrastruktur Konektivitas, Peran Pemerintah, dan Perkembangan Sosial Ekonomi Regional: Bukti dari Kalimantan - Arifin, Bondi; Horisonta, Surya; Juanda, Juanda; Rahman, Arif Budi; Julihandono Sj, Chandra; Atmodjo, Shasza Yemima Puteri; Maulida, Afifah (Journal of Infrastructure Policy and Management (JIPM), 2024)
The Island of Kalimantan, designated by the Indonesian government as the site for the new capital city, necessitates significant infrastructure improvements to support its economic development. This research evaluates the progress of the connectivity infrastructure in Kalimantan, reviews the role of the government in facilitating this development, and estimates the relationship between infrastructure and the community’s social and economic activities. The study applies descriptive statistics, correlation analysis, comparative studies, and interregional input-output methodology by utilizing various data sources including the central government budget, regional government budget, village potential data, Susenas, and Geographic Information System GIS) data. Our findings reveal increasing budgets from both central and local governments, yet limited improvements in road infrastructure. An increase in the availability of road infrastructure per km² is positively correlated with enhanced trading activities, the provision of shops, improved public transportation, and better access to education and health facilities. In addition, the establishment of airports and ports is linked to higher per capita income and increased service and manufacturing activities, as well as the growth of food stalls, shops, and banking services.